2015
DOI: 10.3923/jbs.2015.144.149
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Effective Organic Carbon for Biofloc Shrimp Culture System

Abstract: This study aims to identify an effective carbon source which enhances not only the microbial load but also the shrimps growth. The carbon source cane sugar, molasses and jaggery were tested in 100 L culture tanks with stocking density of 30 mG 2 Peneus monodon seeds for a culture period of 40 days. Jaggery biofloc tank shows highest floc formation (22 mL), highest survival (86%) and highest ABW (6 g), proximate composition of jagerry biofloc had higher protein level (35%) followed by mollases and sugar culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Bacillus from a highly enclosed culture system of Litopenaeus vannamei was isolated [23] . [45] used molasses as source of carbon for developing biofloc for Penaeus indicus post larvae rearing in tank system that showed floc volume of 12 ml/L very close to the present study.…”
Section: Discussionsupporting
confidence: 84%
“…Bacillus from a highly enclosed culture system of Litopenaeus vannamei was isolated [23] . [45] used molasses as source of carbon for developing biofloc for Penaeus indicus post larvae rearing in tank system that showed floc volume of 12 ml/L very close to the present study.…”
Section: Discussionsupporting
confidence: 84%
“…FCR and FER values of the present study showed that fishes reared under jaggery based biofloc system showed lowest FCR and highest FER compared to control fishes which showed the highest FCR and lowest FER. Previous study on jaggery based biofloc system revealed that this technology can reduce the FCR more effectively (Sakkaravarthi and Sankar, 2015). Jaggery has the capability to dissolve quickly in water and helps to develop more microbial load; especially, heterotrophic bacteria upto 13×10 6 counts (Singh et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in earlier studies, higher growth rate was observed in biofloc raised tilapia (Azim and little 2008;Crab et al, 2009), L. rohita (Mahanand et al, 2013;Ahamd et al, 2016), Carassius auratus (Wang et al, 2015) and Cyprinus carpio (Najdegerami et al, 2015), which clearly indicates that biofloc can substitute aquatic animal feed and can promote growth of diverse fish species. Sakkaravarthi and Sankar (2015)…”
Section: Discussionmentioning
confidence: 99%
“…Combination of molasses and algicidal bacteria (CZBCI) controlled the abundance of cyanobacteria in the culture system. The abundance of total bacteria and culturable heterotrophic bacteria increased gradually in all groups Xu et al (Sakkaravar & Sankar 2015). Therefore, the nutritional composition of bioflocs is linked to the composition of the microbiota present in the flocs.…”
Section: Effects Of Carbon Source On Nutritional Quality Of Bioflocsmentioning
confidence: 95%
“…(2019) (Sakkaravar & Sankar 2015). Therefore, the nutritional composition of bioflocs is linked to the composition of the microbiota present in the flocs.…”
Section: Effects Of Carbon Source On Nutritional Quality Of Bioflocsmentioning
confidence: 99%